2009
DOI: 10.1007/s00403-009-0955-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel KIT missense mutation in one Chinese family with piebaldism

Abstract: Piebaldism is an autosomal dominant disorder characterized by congenital leukoderma, mostly affecting forehead, abdomen and knee. Previous studies have revealed that piebaldism is caused by mutations of the KIT gene, which encodes the cell surface transmembrane tyrosine kinase receptor for KIT ligand. We reported here a Chinese Han family with piebaldism, and performed mutation detection of KIT gene by direct sequencing. A novel missense mutation C58G was identified in the patients, but not in the healthy indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
1
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
1
3
1
1
Order By: Relevance
“…Consistent findings were reported by Krüger et al, who found that the allele frequency of the KIT variant M541L was as high as 8.1% in the healthy population, not differing from chronic myelogenous patients (8.3%) [13]. The V530I variant has to our knowledge, never been described so far, in either AF or other KIT-related diseases such as mastocytosis, GISTs or piebaldism, [14, 15]. The exon 10 V530I substitution alters the transmembrane domain of KIT (contained between amino acids 521–543), and was described in acute myelogenous leukemia [16, 17].…”
Section: Discussionsupporting
confidence: 80%
“…Consistent findings were reported by Krüger et al, who found that the allele frequency of the KIT variant M541L was as high as 8.1% in the healthy population, not differing from chronic myelogenous patients (8.3%) [13]. The V530I variant has to our knowledge, never been described so far, in either AF or other KIT-related diseases such as mastocytosis, GISTs or piebaldism, [14, 15]. The exon 10 V530I substitution alters the transmembrane domain of KIT (contained between amino acids 521–543), and was described in acute myelogenous leukemia [16, 17].…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, a severe phenotype showing larger leukoderma is associated with severely damaged migration in embryo. After identification of a missense mutation in the KIT gene on the chromosome 4q12 in a large family, 3 32 missense mutations, 3,29,31–47 17 deletions, 31,34,40,41,43,48–54 four insertions, 31,34,35,43 seven nucleotide splice‐site mutations, 31,34,39,41,43 two nonsense mutations 39,41 and one pericentric chromosomal inversion 55 have been identified in the KIT gene or in the chromosomal region of the KIT gene. These genetic studies indicate that the clinical features and phenotypic severity of piebaldism clearly correlate with the site and the type of mutation in the KIT gene 56 …”
Section: Piebaldismmentioning
confidence: 99%
“…age=markerDetail&key=10603, MGI_4.21). While these mutant sites are mostly located in the intracellular part, except for nonsense mutations, little is known of the extracellular site mutations [5]. Kit W-2Bao mutant is the only known mutant that is located in the extracellular 4th IG-like domain.…”
Section: Structure and Function Of The C-kit Proteinmentioning
confidence: 99%
“…A homologous gene mouse mutation model would be extremely valuable for exploring the mechanisms and therapeutic approaches of Kit related diseases [4][5][6][7].…”
mentioning
confidence: 99%